Review study of kumbh mela as a pilgrimage site - B R Divya; Keshavamurthy (Wolters Kluwer Medknow Publications, 2020)
Pilgrimage site is a testimony to the sacred emergence and integration of space and time with the human spirit. The Kumbh Mela is one of the world's largest Hindu gathering known for bringing auspiciousness and contentment to its believers. The study is an attempt to bring out the significances of Kumbh as an important Hindu pilgrimage site and enumerating its healing dynamics.